Home, Physical Disability and Sense of Belonging in Nina Raine’s Tribes - Nurten Çelik (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Home has traditionally been perceived as a location that provides control, freedom of self-expression, and psychological, social, and physical security. However, the presence and development of physical impairment subvert the positive aspects and conventional conceptions of home. Any corporeal attributes that challenge the culturally assumed views of the disabled body are rarely or never recognized as a part of domestic life. Home transforms into a site of oppression and discrimination as the denial of impairment in the sphere of the home leads to psychological and emotional disturbance and the distortion of a sense of belonging. One contemporary play that explores the complicated relationship between impairment, home, and culture is Nina Raine’s Tribes. Tribes dramatizes the ways in which the cultural understanding and treatment of disability shape and regulate the embodied experiences of the disabled character within the confines of home. Billy’s deafness is ignored by his family members, who do not acknowledge the existence of the deaf community, sign language, and deaf culture. Additionally, Billy experiences alienation and isolation in a family that wallows in miscommunication, disagreement, misunderstanding, and lovelessness. Therefore, this essay explores how the social norms concerning the disabled body operate to determine and govern the perception and validation of hearing impairment in a home setting by focusing on the emotional aspects of an embodied life. Furthermore, it explores how the pre-established notions of the body, hierarchy, and value create feelings of alienation and a lack of belonging.